Study of fetomaternal outcome of teenage pregnancy in a tertiary care hospital-MGMGH - Devi, Gayathrie; ., Kayalvizhi; M., Poovathi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The objective is to study the fetomaternal outcome in teenage pregnancy at MGMGH for the study period of 6 months from April 2018 to September 2018. Teenage pregnancy is a worldwide health problem. WHO defined adolescence as the period from 10-19 years. It is a serious health problem in a developing country like India. Teenage pregnancy is associated with high risk of prematurity, low birthweight, preeclampsia and anaemia. The NHFS IV 2015 -2016 estimates that overall teenage pregnancy in India 7.9%. Methods: It is a retrospective study conducted in a tertiary care hospital at MGMGH, Trichy over a period of 6 months.251 teenage pregnant women delivered at our institution were selected for the study out of 4508 total deliveries during the study period. Parameters including incidence, age, parity, booking status, educational and socioeconomic status, medical disorders, antepartum, intrapartum, postpartum complications, mode of delivery and neonatal outcome were studied. Results: Study showed the incidence of teenage pregnancy at our MGMGH is 5.56%. Among these teenage pregnant women 47.1% had anaemia, 23.1% had gestational hypertension,4.8% of women had eclampsia, 22.3% % had preterm delivery. Lscs rate was 27.1%,70.29 % had Normal vaginal delivery,1.6% had instrumental deliveries, 31.5% had low birth weight babies,28.2 % NICU admissions, 2.9% perinatal deaths. Conclusions: Teenage pregnancy is associated with increased incidence of anaemia, pre-eclampsia, eclampsia, preterm delivery, instrumental delivery, low birth weight and perinatal death. By improving socio economic status, education, nutrition, good antenatal care, public awareness, institutional delivery and postnatal care help in reducing maternal and perinatal morbidity and mortality in adolescent pregnancy.